1984
DOI: 10.1159/000120180
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Hydrocephalus: Long-Term Results of Surgical Therapy

Abstract: A personal series of 170 children who underwent 636 operative procedures for hydrocephalus have been followed for 5–12 years. The results of treatment have been analyzed by etiology, years of follow-up, and summarized generally. 5-year survival was 83.5%, current survival is 78.8%. Normal intelligence was found in 63.4% of 5-year survivors, in 64.2% of current survivors. The procedural risk for early shunt infection was 5.8%, while 6.5% of the patients developed a late infection. There is no difference in resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
6

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 14 publications
1
36
0
6
Order By: Relevance
“…Amacher and Wellington reported a 21% death rate over a 5-to 12-year follow-up study. 1 Our high mortality rate (39% in patients without tumors) must be considered in light of the era in which treatment was conducted, that is, before CT scans and without modern diagnostic tools. There was also at the time a lack of established routine controls for assessing persistent shunt function and recognizing shunt malfunctions.…”
Section: Discussion Mortalitymentioning
confidence: 99%
“…Amacher and Wellington reported a 21% death rate over a 5-to 12-year follow-up study. 1 Our high mortality rate (39% in patients without tumors) must be considered in light of the era in which treatment was conducted, that is, before CT scans and without modern diagnostic tools. There was also at the time a lack of established routine controls for assessing persistent shunt function and recognizing shunt malfunctions.…”
Section: Discussion Mortalitymentioning
confidence: 99%
“…1,2,9,10,12,15,17) The present study excluded patients whose age at the last assessment of clinical outcome was less than 1 year. The 10-year survival of surgically treated patients is more than 60%, half of whom live independently and have normal intelligence.…”
Section: Outcomementioning
confidence: 99%
“…However, not all studies have used the same definition of normal intelligence and the composition of the study populations has varied considerably. 1,17,19) Another good measure might be whether the child can attend a normal school or not, as integration into the normal school system was possible for 60% of the children but half of them were 1-2 years behind their age group or having difficulties. 10) The present study could not show better clinical outcome in the shunt group than in the non-shunt group, but suggested that early surgery is optimum for term infants and delay in surgical treatment increase the risk of poor outcome.…”
Section: Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…VPS enfeksiyonlarının insidansının VP takılan olguların tümünde %6.5-23.5 oranında olduğu bildirilmektedir (3)(4)(5)(6)(7)(8)(9) . Enfeksiyon, VPS komplikasyonları arasında en çok korkulan ve şant yetmezliğine en çok neden olan komplikasyondur.…”
Section: Discussionunclassified